Microbiologic diagnostics and pathogen spectrum in infective endocarditis of surgically treated patients: a five-year, retrospective, monocentric study - Ziegler, Renate; Arnold, Hendrik; Bertram, Ralph; Geißdörfer, Walter; Pauschinger, Matthias; Fischlein, Theodor; Pollari, Francesco; Steinmann, Joerg (Infection, 2023)
PurposeThe spectrum of causative organisms in infective endocarditis (IE) has changed significantly in the last decades. Reliable pathogen detection is crucial for appropriate antimicrobial therapy for IE. The aim of the study was to evaluate the diagnostic value of microbiological methods for detecting the causative microorganism of IE and to analyze the spectrum of pathogens.MethodsA total of 224 cases (211 unique patients, some with multiple surgeries) were included into this retrospective study. Patients were diagnosed with IE according to the modified Duke criteria from January 2016 to July 2021 and underwent heart valve surgery in a tertiary hospital. Pathogen detection was performed by blood culture, microbiological culture and 16S rDNA PCR of explanted heart valve material.ResultsA causative pathogen of IE was detected in 95.5% (n = 214) of cases. Blood cultures were positive in 83.3%, while a pathogen in the examined heart valve samples was identified in 32.6% by culture and in 88.2% by 16S rDNA PCR. A microorganism was identified by 16S rDNA PCR in 61.1% of blood culture negative cases but only in 19.4% by heart valve culture. The most common pathogens were Staphylococcus aureus (27%), viridans group streptococci (20%), enterococci (19%) and coagulase-negative staphylococci (CoNS 8%). Cutibacterium acnes (7%) was detected in prosthetic valve IE cases only.ConclusionBlood culture as a comparatively non-invasive and straightforward technique remains an important and reliable method for initial detection of the causative organism in IE. Diagnostic stewardship programs should broadly emphasize proper collection of blood cultures, particularly sampling prior to any antibiotic treatment. Additionally, molecular testing using 16S rDNA tissue PCR can be used with culture techniques to increase the diagnostic yield, especially in the case of a negative blood culture.
CRIS-Team WoS Importer:2023-04-28